Simulation of Nanofluid Flow in Porous Square-Shaped Enclosures - Munshi, M. J. H.; Islam, M. S.; Khandaker, M. R. R.; Hossain, M. S. (Journal of Scientific Research, 2023)
Augmentation of heat transfer can be in so many ways, heat transfer of a nanofluid in a porous is one of the most recent methodologies. In this analysis, the physical properties of water as the base fluid and copper as the nanoparticles exercise. The Finite element method is applied to obtain numerical solutions. The effects of the Darcy number, Richardson number and solid volume fraction of nanofluids on the streamlines, isotherms, dimensionless temperature, velocity profiles, and average Nusselt numbers and average fluid temperature examined graphically. It has found that both the Richardson number and solid volume fraction have a noteworthy influence on streamlines and isotherms. Darcy number has a good control parameter for heat transfer in fluid flow through a porous medium in the enclosure. A heat transfer correlation of the average Nusselt number for various Darcy numbers and solid volume fraction presented here. Finally, for the validation of the existing work, the current results are compared with the published results, and a favorable agreement attained. Besides this, heat transfer in the square enclosure remains better than for the other enclosures with the wavy walls or curved walls.